Arab-Muslim Intellectual Responses to Modernity: Navigating Anxiety and Authenticity in the Thoughts of Muhammad Abid al-Jabiri and Abdurrahman Taha - Widigdo, Mohammad Syifa Amin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This study aims to unfold the intellectual dynamics within modern Arab thought, particularly during the second phase of the Arab Renaissance, which seeks to overcome civilizational anxiety in dealing with modernity. Rather than outlining the broad spectrum of modern Arab intellectual discourses—ranging from Salafists and liberalists to Marxists—this research focuses on the “epistemological approach” introduced and championed by two modern Moroccan philosophers, Muhammad Abid al-Jabiri (referred to as al-Jabiri) and Abdurrahman Taha. By engaging with the intellectual works of al-Jabiri and Taha, this study demonstrates how their readings and approaches to tradition (turath) provide alternative ways of overcoming Arab-Muslim civilizational anxiety and discovering authentic forms of modernity. While al-Jabiri offers a contemporary reading of tradition that advocates the Rushdian spirit, Taha emphasizes the inter-relational, ethical, and practical aspects of tradition necessary for building a solid foundation of Arab-Muslim ethical modernity.